DEVELOPING STUDENTS' ENTREPRENEURIAL SPIRIT THROUGH THE SUBJECT ILMU HITUNG KEUANGAN - Subekti, Retno (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2012)
This article was written to share the experiences of teaching 'trading or doing business' in the subject of Ilmu Hitung Keuangan in 2010. This Article also share about the phenomenon of appeared